Teachers’ Strategies to Handle Disruptive Students in Freedom Writers Movie - Norliani Norliani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
The objective of this research was to find out the teachers’ strategies to handle disruptive students in Freedom Writers movie. This research used descriptive qualitative research. The source of data in this research is obtained from the movie “Freedom Writers”. The instrument of this research is the researcher herself. In collecting the data, the researcher used an analysis document. The data sources documented in this study is in the form of the content in the Freedom Writers movie. Techniques of data analysis  are: watching the movie repeatedly, noting the strategies that the teacher did and, categorizing the data  by using Harmer ‘s theory (2001) and by Hue & Lie (2008) . The finding showed that the teacher applied verbal strategies that proposed by Hue & Lie (2008), from six verbal strategies, the teacher used two strategies namely boosting interest, and calling on students, besides that, the teacher also applied two strategies that proposed by Harmer (2001), they are talk to individual and use activities. with this research hopefully it can provide an overview how to deal with disruptive students in the classroom.